Investigation of nonlinear optical properties of Sudan red G dye solutions using diffraction rings patterns and z-scan technique - Mahdy, Ali; Furat A. Al-Saymari (University of Thi-Qar Journal of Science, 2024)
Nonlinear optical properties of Sudan red G (SRG) dye solutions in DMF solvent at different concentrations using diffraction ring patterns and z-scan techniques were investigated. The samples were exposed to two different wavelengths of light sources, continuous wave laser operating at 532 nm green laser and blue laser operating at 473 nm. The diffraction ring patterns of the SRG solutions at three different dye concentrations and over laser power ranging from 5 to 50 mW have been recorded, showing asignificant nonlinear optical behaviors. The findings show that the number of diffraction rings increases as laser power increases, leading to increase the nonlinear refractive index (n2). It was also observed that when the dye concentration increases from 0.25 mM to 1 mM and at the incident intensity of 6800 W/cm2 , the refractive index increases from 0.78×10-6 to 1.33 cm2/W for the sample exposed by green laser and from 0.48×10-6 to 1.18×10-6 cm2/W for the sample exposed by blue laser. From open and closed aperture z-scan curves, the nonlinear absorption coefficient (β) and nonlinear refractive index of the samples were evaluated at laser intensity of 680 W/cm2. As dye concentration increases from 0.05 mM to 0.1 mM, β increases from ~6.9×10-3 cm/W to ~11.16×10-3 cm/W at wavelength 532 nm and from ~5.78×10-3 cm/W to ~10.08×10-3 cm/W at wavelength 473 nm. Moreover, the value of n2 are increases from ~1.23×10-7 cm2/W to ~4.25×10-7 cm2/W at wavelength 532 nm and from ~0.8×10-7 cm2/W to ~3.33×10-7 cm2/W at wavelengt